Cold-tolerant microorganisms causing spoilage of vacuum-packed beef under time-temperature abuse determined by culture and qPCR. (February 2023) - Dorn-In, Samart; Führer, Laura; Gareis, Manfred; Schwaiger, Karin
Abstract: Vacuum packaging and storage conditions at chilled temperatures are commonly used in order to prolong the shelf life of meat. Under these conditions and time-temperature abuse, cold-tolerant (facultatively) anaerobic spoilage microorganisms can continue growing. This study investigated growth of six relevant spoilage microorganisms in vacuum-packed beef (n = 12, 72 subsamples, stored at 10 °C for 28 days) using culture and qPCR methods. Correspondingly, six qPCRs were newly developed/modified (for total bacteria, lactic acid bacteria (LAB), Enterobacterales, total fungi, Kazachstania psychrophila, and cold-tolerant Clostridium spp.). Besides microbial quantification, four spoilage appearances of meat (gas production, spoilage odor, % drip loss, and meat color) were observed. Results obtained from culture and qPCR show that total bacteria, LAB, and Enterobacterales reached their stationary phase at day 7 when spoilage parameters such as gas production were statistically increased and a deviation of odor was detected. Fastidious cold-tolerant Clostridium spp. and K. psychrophila could be detected from day 7. Based on microbiological and sensory analysis results, the maximum shelf life of vacuum-packed beef stored at 10 °C is 7 days. The developed qPCR has the potential to be used as an alternative method to culturing for determination of microbial growth. Highlights: Six qPCRs were developed and successfully applied to quantify meat microbiota. Culture results of total bacteria and LAB correlate with three spoilage parameters. Cold-tolerant clostridia and yeasts were detected in 17% and 25% of beef samples. Maximum shelf life of vacuum-packed beef stored at 10 °C was determined to be 7 days.